2021
DOI: 10.3389/fphar.2020.605823
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of Aflatoxins Induces Severe Hepatotoxicity Through Multiple Mechanisms

Abstract: Aflatoxins (AFs) are commonly contaminating mycotoxins in foods and medicinal materials. Since they were first discovered to cause “turkey X” disease in the United Kingdom in the early 1960s, the extreme toxicity of AFs in the human liver received serious attention. The liver is the major target organ where AFs are metabolized and converted into extremely toxic forms to engender hepatotoxicity. AFs influence mitochondrial respiratory function and destroy normal mitochondrial structure. AFs initiate damage to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 127 publications
(282 reference statements)
1
20
0
Order By: Relevance
“…AFB1 destroys the normal structure of hepatocytes and mitochondria, subsequently altering the antioxidant system. Furthermore, autophagy eliminates impaired cellular structures and apoptosis is initiated by liver hepatocytes to maintain liver function; however, it also causes hepatotoxicity (7)(8)(9). The metabolic and toxic effects of AFB1 are principally observed in liver tissues, and previous studies have suggested that hepatic cell apoptosis leads to liver damage in poultry.…”
Section: Introductionmentioning
confidence: 99%
“…AFB1 destroys the normal structure of hepatocytes and mitochondria, subsequently altering the antioxidant system. Furthermore, autophagy eliminates impaired cellular structures and apoptosis is initiated by liver hepatocytes to maintain liver function; however, it also causes hepatotoxicity (7)(8)(9). The metabolic and toxic effects of AFB1 are principally observed in liver tissues, and previous studies have suggested that hepatic cell apoptosis leads to liver damage in poultry.…”
Section: Introductionmentioning
confidence: 99%
“…Naturally occurring AFs (AFB 1 , AFB 2 , AFG 1 , and AFG 2 ) act as strong carcinogens, thus they are assigned into Group 1 "carcinogenic to humans" by the International Agency for Research on Cancer (IARC) [84,105]. Apart from their carcinogenicity, they have been reported to have mainly hepatotoxic, genotoxic, mutagenic, teratogenic, immunosuppressive, nephrotoxic, and cytotoxic effects [106][107][108][109].…”
Section: Recent Data On Aflatoxin Toxicitymentioning
confidence: 99%
“…Furthermore, the effects of FB1 on liver damage and inflammation were consistent with an inhibition of the wellknown pro-inflammatory and pro-apoptotic effects of sphingolipid species respectively such as S1P and sphingoïd bases (Molino et al, 2017;Riley et al, 2001). Therefore, the proinflammatory effects of FB1 observed in HFD-fed mice might have occurred as an indirect consequence of altered ceramide homeostasis (Chen et al, 2021). Alternatively, high FB1 exposure may exert toxic effects in hepatocytes that are independent of ceramide metabolism, but reflect a mechanism yet to be determined.…”
Section: Dixon Et Al 2021)mentioning
confidence: 99%
“…The most common symptoms are nephrotoxicity, hepatotoxicity (Terciolo et al, 2019), immunotoxicity (Devriendt et al, 2009;Halloy et al, 2005), and intestinal barrier function disturbances (Bouhet et al, 2006;Loiseau et al, 2007). To date, the known molecular mechanisms underlying FB1 toxicity are mostly related to its inhibitory effect on sphingolipid biosynthesis (Wang et al, 1991;Chen et al, 2021). Indeed, FB1 and sphingoid long-chain bases share similar structural backbone features.…”
Section: Introductionmentioning
confidence: 99%